Evaluation of beef top sirloin steaks of four quality grades cooked to three degrees of doneness - Olson, Brittany A. (Kansas State University, 2019)
The objective of this study was to evaluate the impact of quality grade on beef eating quality of top sirloin steaks when cooked to multiple degrees of doneness (DOD). Beef top sirloin butts (N = 60; 15 / quality grade) were collected to equally represent 4 quality grades [Prime, Top Choice (modest⁰⁰ – moderate¹⁰⁰), Low Choice, and Select]. Top butts were cut into six consecutive steaks, and then divided laterally to get a total of twelve steaks per top butt. Steaks were assigned to one of three DOD: rare (60°C), medium (71°C), and well-done (77°C). Steaks within DOD were assigned to consumer sensory analysis, trained sensory analysis, fat and moisture analysis, and Warner-Bratzler shear force (WBSF). There were no interactions (P > 0.05) for all consumer ratings of palatability traits, indicating increases in DOD had the same impact across all quality grades. There was a difference (P > 0.05) within quality grade for consumer ratings of juiciness (P > 0.05). Prime steaks had greater (P < 0.05) juiciness ratings than all other quality grades, except for Top Choice. As DOD increased, consumer ratings and the percentage of steaks rated acceptable for each palatability trait decreased (P < 0.05; rare > medium > well-done). There was a quality grade × DOD interaction (P < 0.05) for trained sensory panel juiciness scores. When cooked to medium, Prime and Top Choice steaks were rated higher (P < 0.05) for juiciness than Low Choice and Select steaks. Similar to consumer ratings, trained panel ratings of tenderness decreased (P < 0.05) as DOD increased (rare > medium > well-done). Lastly, there were no quality grade by DOD interactions (P > 0.05) for Warner-Bratzler shear force. These results indicate that regardless of the DOD steaks were cooked to, quality grade had minimal impact on the palatability of beef top sirloin steaks. Therefore, unless cooked to a medium DOD, it is unnecessary for consumers, retailers, and foodservice to pay premium prices for higher quality top sirloin steaks, as the same eating experience will be given.
Keywords: Beef; Consumer; Degree of doneness; Palatability; Marbling; Top sirloin steaks